The investments : an American conspiracy - Berube, Clair T. (Emerald Publishing Limited : Information Age Publishing, 2020)
"This book is a radical departure of most on the market because it takes American institutions, beginning and ending with public education, and exposes how dysfunction and the investment in this dysfunction is an actual political agenda item. The Investments focuses on the capitalization, privatization and dismantling of public education, and how other social systems such as for-profit prisons, healthcare (or the lack thereof), racism and current immigration issues, the investment in criminalizing people called "the other", and the military/industrial complex are co-dependent and how the destruction of public education affects the other institutions. Each has a toxic connection and reliance to each other. Each chapter will delve into the rigging that takes place to purposefully attempt to cripple public education and consciously create a permanent underclass, usually without the knowledge of the general public; and the egos, identities and sinister political forces behind such manipulation. Education is the hub of this book: because public education is the best vehicle for democracy American has ever known, and therefore, unbeknownst to many Americans, in the crosshairs. There is a vast conspiracy for power and control going on in our country; and many Americans are ignorant of the conspiracy"--